Development of a Marketplace Building Store Using a Value Proposition Design Approach (Case Study: XYZ.COM) - Muhammad Septian Widaryanto; Astri Ghina (Transpublika Publisher, 2025)
This research is designed with the aim of identifying the various problems that are commonly faced by users of the XYZ.com building materials marketplace and, at the same time, developing appropriate solutions by applying the Value Proposition Design approach in order to address those problems more effectively. The main challenges that XYZ.com is currently experiencing are related to user adoption as well as overall user satisfaction, which then become the primary focus and central concern of this research. In conducting the study, qualitative research methods were employed, with data collection carried out through in-depth interviews combined with observation activities to obtain richer insights. This research is also grounded in the pragmatism paradigm, which emphasizes practical considerations in problem-solving. The expected contribution of this research is not only to provide practical recommendations that can enhance XYZ.com’s services but also to add valuable insights to the existing literature on e-commerce platform development in Indonesia.